93.3k views
5 votes
I’m not all to sure what to do here, anyone know??
(pic included)

I’m not all to sure what to do here, anyone know?? (pic included)-example-1
User Doran
by
5.6k points

1 Answer

3 votes
Hello there!

To solve those questions, you only have to substitute the number inside the parenthesis into x.

f(x) = x² + 1

f(-2) = (-2)² + 1
4 + 1
f(-2) = 5

f(0) = 0² + 1
f(0) = 1

f(1) = 1² + 1
1 + 1
f(1) = 2

So your answers are....
f(-2) = 5
f(0) = 1
f(1) = 2

Hope this helped!! :)
User Ezvine
by
5.9k points